2017
DOI: 10.1167/17.8.3
|View full text |Cite
|
Sign up to set email alerts
|

Using optic flow in the far peripheral field

Abstract: Self-motion information can be used to update spatial memory of location through an estimate of a change in position. Viewing optic flow alone can create Illusory self-motion or "vection." Early studies suggested that peripheral vision is more effective than central vision in evoking vection, but controlling for retinal area and perceived distance suggests that all retinal areas may be equally effective. However, the contributions of the far periphery, beyond 90°, have been largely neglected. Using a large-fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…(However, their temporal phase task proved much more difficult when the alternating motions were orthogonal-vertical and horizontal-something not observed for our speed-discrimination task ( Fig 2C)). More generally, our finding that observers can compare the speeds of well separated arrays is consistent with the ability of observers to recognize global motion in a distributed array [53], with the evidence for cooperative processes between motions in different parts of the field [54] and with the important role of bilateral optic flow in balance and vection [31,55].…”
Section: Plos Onesupporting
confidence: 82%
See 1 more Smart Citation
“…(However, their temporal phase task proved much more difficult when the alternating motions were orthogonal-vertical and horizontal-something not observed for our speed-discrimination task ( Fig 2C)). More generally, our finding that observers can compare the speeds of well separated arrays is consistent with the ability of observers to recognize global motion in a distributed array [53], with the evidence for cooperative processes between motions in different parts of the field [54] and with the important role of bilateral optic flow in balance and vection [31,55].…”
Section: Plos Onesupporting
confidence: 82%
“…The primary roles of cells sensitive to motion contrast are thought to lie in the segregation of figure from ground, in the estimation of depth and form from motion parallax, and in the analysis of optic flow fields for the maintenance of balance and the guidance of locomotion [see e.g. 19,21,29,30,31]; and not all such cells exhibit tuning for speed [21,28]. However, if the discrimination of speed did depend on signals from intrinsically local comparators of motion, we might expect performance to deteriorate with increasing spatial separation of the stimuli.…”
Section: The Present Experimentsmentioning
confidence: 99%
“…Yet, our results regarding biases are qualitatively similar to those of previous studies, even though those studies tested motion along a one dimensional hallway. Specifically, studies that tested visual path integration over short distances found that subjects overshoot the target (Frenz and Lappe, 2005; McManus et al, 2017) while studies that used long-range targets found the opposite (Brossard et al, 2016; Lappe et al, 2007; Redlick et al, 2001). A noteworthy departure from past studies was observed in the manner by which variability of our subjects’ responses scaled with distance.…”
Section: Discussionmentioning
confidence: 99%
“…The human infant becomes progressively able to explore the surrounding space more independently with the amount of visual information actively gathered growing dramatically. Peripheral vision plays a role in balance adjustments and the optical flow happening in the visual periphery seems to be essential for a stable standing position (Horiuchi et al., 2017) and for walking (McManus et al., 2017). Also, being sensitive to moving visual targets across the visual field is critical to detect potential threats and to guide the infant's exploratory behavior.…”
Section: Discussionmentioning
confidence: 99%